Hyaluronic acid hydrogels incorporating platelet lysate enhance human pulp cell proliferation and differentiation - Almeida, Leopoldina D. F.; Babo, Pedro S.; Silva, Cristiana R.; Rodrigues, Márcia T.; Hebling, Josimeri; Reis, Rui L.; Gomes, Manuela E. (Springer Nature, 2018)
The restoration of dentine-pulp complex remains a challenge for dentists; nonetheless, it has been poorly addressed. An ideal system should modulate the host response, as well as enable the recruitment, proliferation and differentiation of relevant progenitor cells. Herein was proposed a photocrosslinkable hydrogel system based on hyaluronic acid (HA) and platelet lysate (PL). PL is a cocktail of growth factors (GFs) and cytokines involved in wound healing orchestration, obtained by the cryogenic processing of platelet concentrates, and was expected to provide the HA hydrogels specific biochemical cues to enhance pulp cells’ recruitment, proliferation and differentiation. Stable HA hydrogels incorporating PL (HAPL) were prepared after photocrosslinking of methacrylated HA (Met-HA) previously dissolved in PL, triggered by the Ultra Violet activated photoinitiator Irgacure 2959. Both the HAPL and plain HA hydrogels were shown to be able to recruit cells from a cell monolayer of human dental pulp stem cells (hDPSCs) isolated from permanent teeth. The hDPCs were also seeded directly over the hydrogels (5 × 104 cells/hydrogel) and cultured in osteogenic conditions. Cell metabolism and DNA quantification were higher, in all time-points, for PL supplemented hydrogels (p < 0,05). Alkaline phosphatase (ALPL) activity and calcium quantification peaks were observed for the HAPL group at 21 days (p < 0,05). The gene expression for ALPL and COLIA1 was up-regulated at 21 days to HAPL, compared with HA group (p < 0,05). Within the same time point, the gene expression for RUNX2 did not differ between the groups. Overall, data demonstrated that the HA hydrogels incorporating PL increased the cellular metabolism and stimulate the mineralized matrix deposition by hDPSCs, providing clear evidence of the potential of the proposed system for the repair of damaged pulp/dentin tissue and endodontics regeneration.